<em>Answer:</em>
n²+3
<em>Explanation:</em>
The differences between the terms are not the same, so this is not "linear". Knowing that the sequence may have started with a 1, you can try subtracting the first number with a number to get 1, and use that number to subtract the rest.
4 - 3 = 1
7 - 3 = 4
12 - 3 = 9
19 - 3 = 16
28 - 3 = 25
In this case, subtracting 3 to all the numbers gave us perfect squares! So this means the nth term has to do with squaring the number and adding three afterward! This can be checked.
√1 = 1
√4 = 2
√9 = 3
√16 = 4
√25 = 5
As we found the values of these terms by subtracting three first and then finding its square root, the nth term will be the opposite; squaring and then adding three! Again, this can be checked!
1² + 3 = 4
2² + 3 = 7
3² + 3 = 12
4² + 3 = 19
5² + 3 = 28
Hope this helps !! :D
-5x + y = -5.....multiply by -2
-4x + 2y = 2
---------------
10x - 2y = 10 (result of multiplying by -2)
-4x + 2y = 2
-----------------add
6x = 12
x = 12/6
x = 2
-5x + y = -5
-5(2) + y = -5
-10 + y = -5
y = -5 + 10
y = 5
solution is (2,5)
Answer:
D
Step-by-step explanation:
Can you give more details please
Answer:
17.37
Step-by-step explanation:
y varies inversely as the square root of x
Mathematically:
y = k.root x
We first find k here
To find k, we were made to know that y is 21 and x = 361
k = y/root.x
k = 21/root. 361
k = 21/19
now what is y when x = 247
From y = k.root x
y = 21/19 * root 247
y= 21/19 * 15.72
y = 17.37